Effects of asparaginase-associated pancreatitis in children with haematological tumours - Tang, Hui-jiao; Chen, Chang-cheng; Hu, Wen-ting; Shen, Shu-hong; Zeng, Jing-qing; Ding, Sheng (Frontiers in Oncology, 2024)
BackgroundAsparaginase-associated pancreatitis (AAP) is a major challenge for continuing asparaginase therapy. We aimed to investigate the acute and long-term complications and survival rates related to first and second AAP episodes in Chinese children with haematological malignancies.MethodsWe retrospectively analysed clinical data of children with pancreatitis who received asparaginase chemotherapy for acute lymphoblastic leukaemia (ALL), acute mixed cell leukaemia, and non-Hodgkin’s lymphoma at Shanghai Children’s Medical Center from November 2013 to November 2023.ResultsOf the 76 children included in the study, 12 had local complications (15.79%), with no deaths recorded. Systemic complications manifested in 28 patients (36.84%), resulting in 3 deaths (3.95%). Four patients (5.26%) developed long-term complications (chronic pancreatitis or insulin-dependent diabetes mellitus). No significant differences in local or long-term complications were recorded between children in the asparaginase re-exposed (n=39) and non-re-exposed (n=45) groups. Among the re-exposed patients, eight (25.81%) experienced a second attack without fatalities or complications. Survival analysis of intermediate- to high-risk patients revealed a significantly higher event-free survival (EFS) rate for the re-exposed group than for the non-re-exposed group. The second AAP episode’s occurrence and severity had no relation to the first AAP episode’s severity, and the second AAP episode was significantly less severe than the first (p<0.001).ConclusionsThe second AAP episode’s occurrence is unrelated to the first AAP episode’s severity, and the second AAP episode’s severity is significantly lower than that of the first. Further, asparaginase therapy could improve EFS in children with intermediate and high-risk ALL.